Little kids first big book of pets - Hughes, Catherine D.; National Geographic Kids (Firm); National Geographic Society (U.S.) (Washington, DC : National Geographic Kids, 2019)
Playful puppies! Cuddly kittens! Beautiful birds! In the next book in the hit Little Kids First Big Book series, readers learn all about pets with fur, feathers, fins, scales, and shells?and how to find and care for the perfect pet for their family. From cats to dogs to guinea pigs to birds to fish to snakes and more, this adorable reference book introduces kids to a wide variety of family-friendly pets. Readers learn which kinds of animals make good pets and which ones are better off staying in the wild, along with how each type of pet eats, sleeps, and plays. Packed with more than 200 colorful photos, the book also provides information on animal breeds, characteristics, and behavior and includes tips for training pets. Filled with fun facts and designed for interactive learning, this book will quickly become a favorite at storytime, bedtime, and any time.
OSLIS\Gale Nat Geo eBooks(2/2/23).
Ages 4-8.
K to grade 3.
Print version record and CIP data provided by publisher; resource not viewed.
Keywords: Pets -- Juvenile literature; Pets; Electronic books- OSLIS; Juvenile works; Electronic books